Sabiston textbook of surgery : the biological basis of modern surgical practice - Sabiston, David C.; Surgical Procedures, Operative; Perioperative care (Philadelphia : Saunders/Elsevier, 2008)
From the Publisher: This distinguished reference carries on a 70-year legacy as the world's most thorough, useful, readable, and understandable text on the principles and techniques of surgery. Its peerless contributors deliver all the well-rounded, state-of-the-art knowledge you need to richly grasp the pathophysiology and optimal management of every surgical condition-so you can make the best clinical decisions, avoid complications, manage unusual situations, and achieve the best possible outcomes. It is a valuable review tool for certification/recertification preparation, and an indispensable source of guidance on overcoming the challenges that arise in everyday practice. As an Expert Consult title, this thoroughly updated 18th edition comes with access to the complete contents online, fully searchable-enabling you to consult it rapidly from any computer with an Internet connection. Provides a more distinguished team of contributors and a better blend of clinical and basic-science information than any other source, providing you with the best possible understanding of the clinical issues surrounding every operative situation. Features a more user-friendly format, a larger and more helpful array of full-color illustrations, and a more versatile and well-constructed web site than other resources-making the answers that you need easier to locate and understand quickly. Offers an organization and content that parallels the written board American Board of Surgery exam, providing excellent preparation for certification and recertification. Includes access to the complete contents online, fully searchable, enabling you to consult it rapidly from any computer with an Internet connection. Incorporates an enhanced emphasis on surgical outcomes to mirror the growing importance of this topic. Delivers comprehensive updates to keep you current with the latest research, techniques, and emerging procedures in the field, as well as completely new chapters on Surgical Patient Safety and Regenerative Medicine.
Includes bibliographical references and index
Keywords: From the Publisher: This distinguished reference carries on a 70-year legacy as the world's most thorough, useful, readable, and understandable text on the principles and techniques of surgery. Its peerless contributors deliver all the well-rounded, state-of-the-art knowledge you need to richly grasp the pathophysiology and optimal management of every surgical condition-so you can make the best clinical decisions, avoid complications, manage unusual situations, and achieve the best possible outcomes. It is a valuable review tool for certification/recertification preparation, and an indispensable source of guidance on overcoming the challenges that arise in everyday practice. As an Expert Consult title, this thoroughly updated 18th edition comes with access to the complete contents online, fully searchable-enabling you to consult it rapidly from any computer with an Internet connection. Provides a more distinguished team of contributors and a better blend of clinical and basic-science information than any other source, providing you with the best possible understanding of the clinical issues surrounding every operative situation. Features a more user-friendly format, a larger and more helpful array of full-color illustrations, and a more versatile and well-constructed web site than other resources-making the answers that you need easier to locate and understand quickly. Offers an organization and content that parallels the written board American Board of Surgery exam, providing excellent preparation for certification and recertification. Includes access to the complete contents online, fully searchable, enabling you to consult it rapidly from any computer with an Internet connection. Incorporates an enhanced emphasis on surgical outcomes to mirror the growing importance of this topic. Delivers comprehensive updates to keep you current with the latest research, techniques, and emerging procedures in the field, as well as completely new chapters on Surgical Patient Safety and Regenerative Medicine; Surgery